2021
DOI: 10.3390/joitmc7020109
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of CRM Activities into e-CRM: The Generating e-Loyalty and Open Innovation

Abstract: Technological developments have digitized consumer behavior all over Indonesia. This has become the basis for the emergence of e-commerce, a digital business system that is widely used by the public in making purchases through apps or websites. For this reason, an e-commerce platform should create e-loyalty, to make it the best option among many stores. This is the first study investigating ten factors that contribute to e-Customer Relationship Management (e-CRM) value on e-loyalty in Indonesia. The study invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…Thirdly, the relationship between E-CRM and customer loyalty was then investigated to examine whether there was any direct linkage between them and the result findings revealed that there was a significant direct impact of E-CRM on customer loyalty (β =0.259, p<0.001). The findings were found to be in consonance with the past literature (Farmania et al, 2021;Kakesh et al, 2021;Khan & Khawaja, 2013;Mang'unyi et al, 2018;Mousavai et al, 2015;Mulyono & Situmorang, 2018;Rashwan et al, 2019;Salehi et al, 2015;Sasono et al, 2021;Shastri et al, 2020) and revealed that if the banks provide better E-CRM services to their customers, their profitable customer base will expand, and the customers will recommend their banks to their friends and relatives, resulting in positive word-ofmouth. Hence, E-CRM has a significant positive impact on customer loyalty.…”
Section: Discussionsupporting
confidence: 87%
“…Thirdly, the relationship between E-CRM and customer loyalty was then investigated to examine whether there was any direct linkage between them and the result findings revealed that there was a significant direct impact of E-CRM on customer loyalty (β =0.259, p<0.001). The findings were found to be in consonance with the past literature (Farmania et al, 2021;Kakesh et al, 2021;Khan & Khawaja, 2013;Mang'unyi et al, 2018;Mousavai et al, 2015;Mulyono & Situmorang, 2018;Rashwan et al, 2019;Salehi et al, 2015;Sasono et al, 2021;Shastri et al, 2020) and revealed that if the banks provide better E-CRM services to their customers, their profitable customer base will expand, and the customers will recommend their banks to their friends and relatives, resulting in positive word-ofmouth. Hence, E-CRM has a significant positive impact on customer loyalty.…”
Section: Discussionsupporting
confidence: 87%
“…The reliability indicators of all our values are above 0.8, the parameters recommended by [96]. In addition, it was also observed that the convergent validity through the analysis of the mean variance extracted in all the constructs exceeded the value of 50% [124]; see Table 1. The amount of variance that a construct captures from its indicators (AVE) must be greater than the variance that said construct shares with the other indicators of the model (squared correlation between the two constructs).…”
Section: Measurement Modelmentioning
confidence: 52%
“…Literature Review E-Customer Relationship Management E-Customer Relationship Management (Concept, Importance) E-CRM is one of the marketing trends that represented a clear response to digital customer behavior and E-business that has been rapidly growing in the current era (Saurabh, 2018;Taghipourian & Hatami, 2019;Farmania, 2021), this perspective shaped the modern image of traditional CRM that has always aimed to anticipate, understand and manage customer requirements (Alqershi et al, 2020). The contributions of researchers and writers to the definition of E-CRM have varied, some consider it just a strategy or tool that can be used as a guide in managing customer relations (Savitri, 2020).…”
Section: Study Questionsmentioning
confidence: 99%
“…Today, digital features dominate many customer experiences so that their expectations go beyond obtaining acceptable services toward superior experiences that enhance the feeling of satisfaction, which confirms that the growing use of the Internet, as well as the rise of digital communication technologies, added more complexity to the customer experience on the part of organizations (Klaus & Maklan, 2012). Hence, business organizations found themselves facing the requirement to adapt to the behavior of the digital customer by reformulating their marketing strategies and employing techniques capable of improving their relationships with customers (Farmania, 2021). The digital transformations made customers more aware of the offers and alternatives available in the market, and thus the extent of their expectations for obtaining distinguished products and services increased, and this seems evident within the banking industry (Abu-Shanab & Anagreh, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation